Comparison of MOG and AQP4 antibody seroprevalence in Korean adults with inflammatory demyelinating CNS diseases. (May 2021) - Hyun, Jae-Won; Lee, Hye Lim; Jeong, Woo Kyo; Lee, Hye Jung; Shin, Jong Hwa; Min, Ju-Hong; Kim, Byoung Joon; Kim, Seung Woo; Shin, Ha Young; Oh, Jeeyoung; Kim, Woojun; Shin, Hyun-June; et al.
We aimed to compare seroprevalence of anti-myelin oligodendrocyte glycoprotein (MOG) and anti-aquaporin-4 (AQP4) antibodies in Korean adults with inflammatory demyelinating diseases (IDDs) of the central nervous system (CNS), based on a multicenter nationwide database. Sera were analyzed using a live cell–based assay for MOG and AQP4 antibodies. Of 586 Korean adults with IDDs of the CNS, 36 (6.1%) and 185 (31.6%) tested positive for MOG and AQP4 antibodies, respectively. No participant showed double positivity. Seroprevalence of MOG antibodies was about five times lower than that of AQP4 antibodies in a large cohort of Korean adults with IDDs of the CNS.